2009
DOI: 10.1097/qai.0b013e3181acff91
|View full text |Cite
|
Sign up to set email alerts
|

Using Social Networks to Recruit an HIV Vaccine Preparedness Cohort

Abstract: Objective Evaluate a social network approach to develop an adolescent cohort for HIV vaccine preparedness and investigate characteristics that influence recruitment. Methods We summarize baseline data from a prospective cohort study that included four sessions over six months. Fifty-nine HIV-infected adolescent and adult patients of a family-based HIV clinic named significant others and indicated willingness to involve them in this study. Sixty-two adolescent and adult significant others not known to be HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…This study raises important topical and methodological areas for further research. Consistent with previous studies [19, 22], the data demonstrate that future research should include measures of respondents’ selectivity in communicating about HIV vaccination, specifically assessing to whom they would promote vaccination and/or trial participation. This study also highlights the need to explore risk compensation intentions among those willing to promote the vaccine.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This study raises important topical and methodological areas for further research. Consistent with previous studies [19, 22], the data demonstrate that future research should include measures of respondents’ selectivity in communicating about HIV vaccination, specifically assessing to whom they would promote vaccination and/or trial participation. This study also highlights the need to explore risk compensation intentions among those willing to promote the vaccine.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have demonstrated the ability of a few index individuals to encourage trial participation among a vast number of peers [18, 22], but the present study is the first to use a social network approach to examine intended peer-promotion of an approved HIV vaccine. In the current study, 433 participants reported willingness to encourage vaccination in 1,076 relationships.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, two qualitative studies reported financial compensation as a key motivator for trial participation, along with altruistic motives and positive peer communication and support (23, 24). Despite evidence that peer communication and support can play a role in promoting participation in HCV and HIV clinical trial research (20, 23, 26), no study to date has explored feasibility of involving peer-promotion in HCV trial recruitment among drug users.…”
mentioning
confidence: 99%